THE REPRESENTATION OF IRAN-SAUDI CONFLICT IN THE NEWSPAPERS REGARDING MINA HAJJ STAMPEDE 2015: A Critical Discourse Analysison the Arab News and Tehran Times - Al-Rawafi, Abdulkhaleq Ali Ahmed (2016)
The Hajj of 2015 showed a significance flashpoint of the long-term history of tension between Tehran (Iran) and Riyadh (Saudi Arabia). Iran and Saudi Arabia exchanged the accusation of standing behind the tragedy of Hajj stampede in Minna, Saudi Arabia. The representation of the tension in the media becomes the focus of the present study, which examines the representation of the Iran-Saudi conflict on Hajj stampede of 2015 in two newspapers, namely the Arab News and the Tehran Times. More specifically, this study examines (1) how the Iran-Saudi conflict regarding the Mina Hajj Stampede of 2015 is represented in the Arab News newspaper, (2) how the Iran-Saudi conflict regarding the Mina Hajj Stampede of 2015 is represented in the Tehran Times newspaper, and (3) the ways in which the Islamic ideological competition between Iran and Saudi Arabia for taking the Islamic leadership in the Arabic world is represented in the Arab News and Tehran Times newspapers regarding Mina Hajj Stampede of 2015. This study uses Critical Discourse Analysis as the main framework, focusing on the analysis of macrostructures developed by Van Dijk (1977, 1980, and 1983). Three texts have been chosen from each newspaper and the macro-rules (selection, deletion, generalization, and construction) have been applied to reduce the information in the micro-level into macro-propositions in the macro-level or the global topics/themes of the discourse. The results show that the Tehran Times newspaper has represented Saudi Arabia more negatively by 66.7% than the Arab News, which represented Iran negatively by 50% of the total texts. This indicates the ideological boundary between 'US' and 'THEM' in both newspapers. In addition, the results show that there is an Islamic ideological competition for taking the Islamic leadership between the Shi'a ideology of Iran and the Sunni Wahabi of Saudi Arabia in the Middle East and the Arab World. The study suggests that the discourse of Hajj be separated from the political discourse between Iran and Saudi Arabia because whenever there is a political tension, a Hajj conflict tends to occur.